2014
DOI: 10.1007/s12031-014-0448-7
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 Signaling via the PI3K/Akt Pathway Confers Neuroprotection in Human Retinal Pigment Epithelial Cells Exposed to Sodium Nitroprusside Insult

Abstract: The pathological increase in the levels of the second messenger nitric oxide (NO) in the vitreous cavity and retina leads to injury and cell death of the retinal pigment epithelium (RPE) cells and eventually may contribute to the occurrence and development of diabetic retinopathy. In this study, we developed a cellular model of retinopathy using D407 cells (a human RPE cell line) exposed to sodium nitroprusside (SNP) and investigated the protective effect of the insulin-like growth factor-1 (IGF-1) towards thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…For example, pathogenic activation of AKT is evident in fibroblasts and macrophages isolated in a murine model of bleomycin-induced lung fibrosis or in fibroblasts of IPF patients (31,33,57). In contrast, PI3K/AKT signaling is required to attenuate oxidant-induced cell injury in lung epithelial, retinal pigment epithelial, and neuronal cell injury, including asbestos-induced AEC apoptosis (2,34,41,54). AKT deficiency promotes oxidative DNA damage by decreasing DNA repair in renal cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…For example, pathogenic activation of AKT is evident in fibroblasts and macrophages isolated in a murine model of bleomycin-induced lung fibrosis or in fibroblasts of IPF patients (31,33,57). In contrast, PI3K/AKT signaling is required to attenuate oxidant-induced cell injury in lung epithelial, retinal pigment epithelial, and neuronal cell injury, including asbestos-induced AEC apoptosis (2,34,41,54). AKT deficiency promotes oxidative DNA damage by decreasing DNA repair in renal cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt signaling pathways mediate cell death or survival, differentiation, and apoptosis responses [40,41]. PC12 and SH-SY5Y cells exposed to cadmium showed reduction in PTEN, resulting in increased PI3K/Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Human retinal pigment epithelial cells (D407 cells) were maintained in 75 cm 2 tissue culture flasks in DMEM supplemented with 10% FBS, streptomycin 100 μg·mL −1 and penicillin 100 U·mL −1 and incubated at 37°C with 5% CO 2 humidified atmosphere. Stock cells were sub‐cultured twice a week to provide new stocks and cells for the experiments described (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…This action of IGF‐1 occurs via the ubiquitous PI3K/ signalling pathway, although the complete pathway including upstream and downstream effectors is yet to be fully characterized (Zheng et al, ; Zheng and Quirion, , ; Sun et al, ; Wang et al, ). In the present study, we evaluated the toxic effect of amiodarone on D407 cells (a human RPE cell line) (Kennedy et al, ; Wang et al, ) and used a clinically relevant cellular model of oxidative injury to evaluate the role of IGF‐1 and its mechanism of action in the protection of D407 cells from the oxidative injury induced by amiodarone. We found that amiodarone inhibited the activation of Akt and induced apoptosis in D407 cells while IGF‐1 promoted the survival of D407 cells subjected to amiodarone‐induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%